Liver-derived extracellular vesicles: A cell by cell overview to isolation and characterization practices - Zivko, Cristina; Fuhrmann, Gregor; Luciani, Paola (Biochimica Et Biophysica Acta-General Subjects, 2021)
Background: Extracellular vesicles (EVs) are a diverse group of membrane-bound nanovesicles potentially released by every cell. With the liver's unique ensemble of cells and its fundamental physiological tasks, elucidating the role of EV-mediated hepatic cellular crosstalk and their role in different pathologies has been gaining the attention of many scientists. Scope of review: The present review shifts the perspective into practice: we aim to critically discuss the methods used to purify and to biochemically analyse EVs from specific liver resident cells, including hepatocytes, hepatic stellate cells, cholangiocytes, liver sinusoidal endothelial cells, Kupffer cells, liver stem cells. The review offers a reference guide to current approaches. Major conclusions: Strategies for EV isolation and characterization are as varied as the research groups performing them. We present main advantages and disadvantages for the methods, highlighting common causes for concern, such as FBS handling, reporting of cell viability, EV yield and storage, differences in differential centrifugations, suboptimal method descriptions, and method transferability. We both looked at how adaptable the research between human and rodent cells in vitro is, and also assessed how well either of them translates to ex vivo settings. General significance: We reviewed methodological practices for the isolation and analysis of liver-derived EVs, making a cell type specific user guide that shows where to start, what has worked so far and to what extent. We critically discussed room for improvement, placing a particular focus on working towards a potential standardization of methods.
CRIS-Team Scopus Importer:2021-06-29
Keywords: Clinical translation; Exosomes; Liver cells; Microvesicles; PEGprecipitation; Ultracentrifugation